PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS XI IPS TENTANG MATERI BIOSFER DI SMA - Gregorius Agung Malik (Unika Santu Paulus Ruteng, 2018)
The objectives of this research are: (1) to know the application of cooperative learning model of think pair share to increase student activity and learning outcomes, and (2) to know the development of activity and learning result of class student about biosphere matter. The method used is the test of learning and observation. The results showed that teacher performance in cycle I was in the high category of 70.16%, and increased again in cycle II was in the high category of 94.35%. The performance of students also increased from cycle I to cycle II of student activities assessed during the learning process on affective aspects, cognitive aspects and psychomotor aspects. Average for affective aspect in cycle I is 73,16% while cycle II is 90,66%, cognitive aspect in learning cycle I is 72,80 percent while cycle II 90,40%, and psychomotor aspect in learning cycle I that is 66.13% and in the second cycle is in good category also that is 90,40%. Thus the test results also experienced an increase in student learning outcomes in the first cycle, the test value of the average grade of classical learning completeness 62.50% is in the category of moderate, and increased again in cycle II is in the high category with classical learning completeness 91.67% . Thus, the low learning outcomes of students on biosphere materials have improved learning outcomes after the application of cooperative learning model type think pair share. In addition, the improvement of student learning outcomes, with cooperative learning model type think pair share make learners more active in following teaching and learning activities.